Surveillance for severe acute respiratory infections in the 2019/2020 season in Tuscany, Italy. (20th October 2021) - Capitani, E; Montomoli, E; Camarri, A; Capecchi, PL; Nante, N; Mannini, I
Abstract: Background: Influenza is a major public health burden. In Italy there were 7.6 million symptomatic case of influenza in the 2019/2020 influenza season. In Italy, the influenza season lasts from October to April of the following year. We analysed influenza A and B viruses from hospitalized patients with Severe Acute Respiratory Infections (SARI) to carry out epidemiological and virological surveillance. Methods: 68 oropharyngeal swabs were taken from the patients with SARI at Le Scotte University Hospital in Siena and they were given a questionnaire to record their underlying disease and vaccination status. Total RNA was extracted from the swabs by means of the QIAamp Viral RNA Mini kit and RT-PCR was carried out. After, biodirectional DNA sequencing reactions were performed. All statistical analyses were performed by means of GraphPad Prism 6 software. Results: The median age of subject was 82 years and 52.9% were female. The subjects showed fever (89.7%), fatigue (77%), headache (47%), cough (75%), sore throat (70.5%), breathlessness (63.2%).We found that 20.5% of 68 subject were positive (13% for A H3N2 and 7% for A H1N1). Out of the 68 subject, 25% received seasonal influenza vaccination (91.6% trivalent vaccine and 8.4% quadrivalent vaccine). The most common underlying disease found in the positive subjects were cardiovascular diseases (50%), renal diseases (50%), lung diseases (42.8%), diabetes (35.7%), cancer (35%). Conclusions: Epidemiological and virological surveillance remains an essential tool for monitoring virus circulation and possible mismatches with seasonal vaccine strains, and providing information that can be used to improve the composition of influenza vaccines. Our data support the importance of seasonal vaccination in subjects with chronic diseases to reduce hospitalisation and mortality. Key messages: Virological surveillance is important for determining the spread of influenza viruses. Seasonal vaccination is considered as the most effective way to prevent influenza and its complications.